A Second Look at Factors Associated with Employer Hiring Behavior Regarding People Who Are Blind or Have Low Vision. (November 2019) - McDonnall, Michele C.; Antonelli, Karla
Introduction: Although negative employer attitudes and reasons that employers do not hire people with disabilities have both been investigated, little research has focused on why employers do hire people with disabilities. The purpose of this study was to investigate factors associated with employer hiring behavior regarding people with visual impairments, including the opportunity to hire (i.e., application receipt). Method: Participants were a national sample of 388 hiring managers who completed an online survey that assessed their hiring experiences concerning people with visual impairments. Two logistic regression models were analyzed, one that included nine independent variables thought to be associated with hiring (Model 1) and one that included these nine variables plus application receipt (Model 2). Results: Variables that were significantly associated with hiring behavior in Model 1 were prior communication with vocational rehabilitation (VR) professionals, employer attitudes, company size, company policy, and personal relationship with someone with a visual impairment. Significant variables in Model 2 were received application, employer attitudes, and personal relationship. Discussion: As expected, application receipt was the most important predictor of hiring behavior, with odds of hiring increasing by more than 40 with receipt of an application. Despite this exceptionally strong relationship, employer attitudes and having a personal relationship remained significant predictors, indicating the robustness of attitudes as a determinant of why employers hire and the importance of personal connections to hiring behavior. Implications for practice: Employers cannot hire unless given the opportunity, and the first step to being hired is typically submitting an application. VR professionals should both encourage consumers to submit applications, providing support in this process as needed, and communicate with employers to encourage their consideration of these applications.